Role of phonon mode in the enhancement of ferroelectric polarization in a perovskite-based eco-friendly functional material - Dubey D.N.; Singh G.; Singh A.K.; Tripathi S. (My University, 2025)
We report here the role of component freezing of three-dimensional polar ( ) phonon mode corresponding to the center of cubic Brillouin zone in tuning the structure-property correlations of a scientifically enriched and technologically important barium-titanate-based eco-friendly functional material (Ba0.92Ca0.08)(Zr0.05Ti0.95−x Snx )O3; BCZTSnx synthesized via solid-state reaction method. The combined X-ray diffraction, Raman spectroscopic analysis, and temperature-dependent dielectric studies have revealed the presence of several crystallographic phase transitions with coexisting phases, viz., , as a function of Sn(x) content. These crystallographic phases, viz., P4mm, Amm2, and R3m results due to freezing of the component(s) of phonon mode (belonging to space group), with the respective order parameter directions (0,0,a), (a,a,0), and (a,a,a) leading to ferroelectric polarization along , and directions, respectively. The ceramic composition corresponding to exhibits a significant reduction in the coercive field (E c ) and an enhancement in ferroelectric polarization (P r ) in comparison to , inferred from PE loop measurements. The enhancement in ferroelectric polarization at has been attributed to the inter-ferroelectric three-phase coexistence around this composition and significantly enhanced amplitudes of ferroelectric phonon modes corresponding to orthorhombic and rhombohedral phases, calculated using the symmetry mode analysis technique. The existence of a high ferroelectric polarization and low coercive field may lead to composition as an eco-friendly candidate for ferroelectric memory devices. Copyright © 2022 EPLA.